Manajemen Sumber Daya Manusia Tenaga Layanan Kependidikan Laboran Terhadap Peningkatan Kualitas Proses Belajar Mengajar Praktik di SMK - Suwandi Suwandi; Musyarapah Musyarapah (Indo Publishing, 2026)
This case study aims to analyze the impact of human resource management (HRM) on improving the quality of teaching and learning practices in vocational high schools (SMK). The development of digital technology demands adaptive, professional, and digitally competent management of laboratory staff. This research employed a qualitative approach with a case study in one vocational high school. Data collection techniques included observation, in-depth interviews, and documentation. The results indicate that HRM implementation, including planning, recruitment, competency development, performance assessment, and motivation and rewards, plays a crucial role in improving the quality of learning. Educators and laboratory staff with strong digital literacy are able to optimize the use of technology in learning, such as through interactive media, digital laboratories, and online learning platforms. Furthermore, collaboration between educators and laboratory staff in managing work practices also contributes to improving student skills. However, several obstacles remain, such as limited infrastructure, a digital competency gap, and a lack of ongoing training. Therefore, a sustainable HRM development strategy through training, supervision, and institutional policy support is needed to continuously improve the quality of the teaching and learning process in line with the demands of the digital era.